Microscopic observation of solid-liquid reaction: A novel laboratory approach to teaching rate of reaction - Setiabudi, A.; Wahyudin, A.; Yuliani, G.; Mocerino, Mauro (2017)
The importance of observation in science and science education has triggered this laboratory development study that investigated the value of an observation kit as a new approach to teaching rate of reaction in general chemistry class. The kit consists of a digital microscope, a “chemical reactor”, and a tailor-made computer application and was used to video-record a solid-liquid reaction and to produce a series of two dimensional solid images that indicate the extent of reaction. The two dimensional image areas were calculated by the computer application by assuming that the image area was directly proportional to the solid mass from which a plot of mass versus time could be obtained. These steps have been tested to solid (zinc, iron, calcium carbonate, and magnesium oxide)-liquid (acid solution reaction systems. Reaction of solid magnesium oxide with nitric acid solution resulted in the best images which were transferable to a plot of solid magnesium oxide mass as a function of time. This was used to explain rate of reaction concepts including average, instantaneous, and initial rate. Furthermore, the effect of concentration on reaction rate could also be explained. The generated data allows students to clearly and repeatedly visualize a solid-liquid reaction and relates rates of reaction concepts. The observation kit also allows teachers and students to extend its application into inquiry based experiments. © 2017, Gadjah Mada University. All rights reserved.